The role of magnetic resonance imaging in early prediction of cerebral palsy - Hnatyszyn, Grazyna; Cyrylowski, Lech; Czeszynska, Maria B; Walecka, Anna; Konefal, Halina; Szmigiel, Olimpia; Gizewska, Maria; Dawid, Grazyna (The Turkish Journal of Pediatrics, 2010)
This work was undertaken to assess the usefulness of magnetic resonance imaging (MRI) of the brain for early prognosis of cerebral palsy. The study group included 47 neonates (24 term and 23 preterm) with symptoms of perinatal asphyxia. MRI examinations in term neonates were performed during the first month of life but not before the second week of life, while in preterm neonates MRI data were acquired between 38 and 40 weeks from conception. MRI of the brain demonstrated hypoxic-ischemic findings in all neonates born with perinatal asphyxia who later progressed to cerebral palsy. These results support the hypothesis that MRI performed in the neonatal period plays an essential role in predicting cerebral palsy in both term and preterm neonates, regardless of their gestational age.